Physicochemical Properties Analysis of Three Indexes Pineapple Core Extract Variety MD2 and Morris - Azhari, Muhammad Firdaus; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
Two popular pineapples (Ananas comosus) cultivars that are prized for their distinct flavours and nutritional value are MD2 and Morris. The physicochemical characteristics of pineapple cores from the MD2 and Morris cultivars at three ripeness stages (Indexes 2, 4, and 6) are investigated in this study, focusing on total soluble solids (TSS), pH, titratable acidity (TA), absorbance, moisture content, and texture profile. The results indicate that TSS (°Brix) values were slightly higher in Morris (11.508 ± 0.324) than in MD2 (11.378 ± 0.496), suggesting comparable sweetness levels. pH increased with ripening, with MD2 exhibiting a slightly higher pH (3.8278 ± 0.0630) than Morris (3.7178 ± 0.0307), indicating lower acidity in MD2. TA declined as maturity advanced, confirming acid metabolism during ripening. Juice clarity decreased with maturity, with Morris demonstrating greater clarity than MD2. Pulp content increased with ripening, with Morris containing significantly more pulp (2.1800 ± 0.2215%) than MD2 (1.843 ± 0.415%). Colour analysis revealed significant changes in lightness (L*), redness (a*), and yellowness (b*), with Morris exhibiting a more pronounced yellow hue. Moisture content declined as MD2 matured, while Morris maintained a relatively stable moisture level. Texture profile analysis showed increased firmness with ripening, with Morris (7930 ± 2398 g) being firmer than MD2 (7012 ± 1052 g). The findings provide valuable insights into the effects of variety and maturity on pineapple quality attributes, guiding optimal harvest timing and processing applications.